Step
*
2
1
1
of Lemma
biject-quotient
.....wf..... 
1. A : Type
2. B : Type
3. f : A ⟶ B
4. R : B ⟶ B ⟶ ℙ
5. Inj(A;B;f)
6. ∀b1:B. ∃a:A. ((f a) = b1 ∈ B)
7. EquivRel(B;x,y.x R y)
8. EquivRel(A;x,y.x R_f y)
9. quo-lift(f) ∈ (x,y:A//(x R_f y)) ⟶ (x,y:B//(x R y))
10. Inj(x,y:A//(x R_f y);x,y:B//(x R y);quo-lift(f))
11. b : x,y:B//(x R y)
12. g : b1:B ⟶ A
13. ∀b1:B. ((f (g b1)) = b1 ∈ B)
⊢ g b ∈ x,y:A//(x R_f y)
BY
{ (DVar `b' THEN EqTypeCD THEN Auto) }
1
.....antecedent..... 
1. A : Type
2. B : Type
3. f : A ⟶ B
4. R : B ⟶ B ⟶ ℙ
5. Inj(A;B;f)
6. ∀b1:B. ∃a:A. ((f a) = b1 ∈ B)
7. EquivRel(B;x,y.x R y)
8. EquivRel(A;x,y.x R_f y)
9. quo-lift(f) ∈ (x,y:A//(x R_f y)) ⟶ (x,y:B//(x R y))
10. Inj(x,y:A//(x R_f y);x,y:B//(x R y);quo-lift(f))
11. b : Base
12. b1 : Base
13. b = b1 ∈ pertype(λx,y. ((x ∈ B) ∧ (y ∈ B) ∧ (x R y)))
14. b ∈ B
15. b1 ∈ B
16. b R b1
17. g : b1:B ⟶ A
18. ∀b1:B. ((f (g b1)) = b1 ∈ B)
⊢ (g b) R_f (g b1)
Latex:
Latex:
.....wf..... 
1.  A  :  Type
2.  B  :  Type
3.  f  :  A  {}\mrightarrow{}  B
4.  R  :  B  {}\mrightarrow{}  B  {}\mrightarrow{}  \mBbbP{}
5.  Inj(A;B;f)
6.  \mforall{}b1:B.  \mexists{}a:A.  ((f  a)  =  b1)
7.  EquivRel(B;x,y.x  R  y)
8.  EquivRel(A;x,y.x  R\_f  y)
9.  quo-lift(f)  \mmember{}  (x,y:A//(x  R\_f  y))  {}\mrightarrow{}  (x,y:B//(x  R  y))
10.  Inj(x,y:A//(x  R\_f  y);x,y:B//(x  R  y);quo-lift(f))
11.  b  :  x,y:B//(x  R  y)
12.  g  :  b1:B  {}\mrightarrow{}  A
13.  \mforall{}b1:B.  ((f  (g  b1))  =  b1)
\mvdash{}  g  b  \mmember{}  x,y:A//(x  R\_f  y)
By
Latex:
(DVar  `b'  THEN  EqTypeCD  THEN  Auto)
Home
Index